Research progress of plant extracts in preservation of meat products - LI Hongyan; XU Minglei; ZHAI Saiya (Shipin yu jixie)
Plant extracts contain natural active ingredients, offering benefits such as health, ecofriendliness, and sustainability. Traditional chemical preservatives, however, can contribute to environmental pollution and pose health risks, limiting their suitability for long-term use. This underscores the need for natural, eco-friendly preservative solutions.. Plant polyphenols and essential oil are the primary plant-derived compounds currently applied in the meat industry, valued for their antioxidant and antibacterial properties. These compounds show promise as natural preservatives, potentially replacing chemical options while preserving the sensory quality and extending the shelf life of meat products. In addition to ensuring food safety and supporting essential processing qualities, plant extracts help preserve the sensory attributes of meat products, thereby extending shelf life. This article reviews the primary quality changes meat products undergo during storage and highlights the common preservation techniques. Emphasis is placed on the preservation mechanisms of plant polyphenols and essential oils in meat products, as well as their current applications. This overview aims to provide a theoretical foundation for advancing the development of natural, plant-based preservatives for the meat industry.